Oasis de Baja California Sur México (siglos XVIII-XX) Propiedad y Uso Comunitario en Ecosistemas Aridos. - Antonio Ortega Santos; Micheline Cariño Olvera (Amnis)
During the last five years, a transdiciplinary project –composed with more than 20 people from fields like environmental history, economic history, anthropology, environmental science and landscape ecology– have developed an approach to the functionality of Oasis Lower California (México), taking like starting point, mid XVIIIth century. Attending to write the history of these agroecosystems, insertion in the state-nation building and global economy during the XIXth century, and how oasis-rancheros (farmers) identity was created, vegetable gardens and dry lands functionality that constructed the landscape of the peninsula until nowadays. The main laboratory has been the Oasis Los Comondú, extended in this article, describing how regime of property and management of commons were transformed in the last two centuries, using information from local and national archives as an enriching oral history research. With this last one, the community of Los Comondú related their histories, their “huertas y llanos” (vegetable gardens and plains) to evocate their future in common.